Exploring The Role of the 4Es (Entertainment, Educational, Aesthetic, Escapist) in Enhancing Wellness Tourism Experiences - Warih Wulandari, Lastiani (Pelopor Publikasi Akademika, 2025)
Wellness tourism is an emerging sector within global tourism that emphasizes health awareness, life balance, and holistic well-being. This study explores the intersection of wellness tourism and sustainable practices through the lens of the 4Es framework—entertainment, educational, aesthetic, and escapist experiences. While the demand for transformative travel is increasing, limited research examines how these experiential dimensions contribute to both tourist satisfaction and sustainability goals. This study addresses that gap by analyzing how the 4Es framework can guide the development of wellness tourism experiences that align with environmental and cultural sustainability. Using a qualitative descriptive approach, data were collected through structured interviews and observations at wellness tourism destinations. The analysis reveals that entertainment provides emotional care, education deepens knowledge of health and culture, aesthetic environments promote relaxation through eco-friendly designs, and escapist experiences offer transformative engagement with nature and heritage. These elements collectively support individual well-being while advancing sustainability principles. The findings have practical implications for wellness tourism providers and policymakers. Strategies such as adopting green certifications, applying resource-efficient practices, engaging in community-based tourism, and training empathetic staff are essential for improving service quality and promoting conservation. Moreover, digital marketing and continuous evaluation are key to meeting the evolving expectations of health-conscious travelers. This study contributes to sustainable tourism literature by showing how the 4Es framework can transform wellness tourism into a vehicle for social and environmental responsibility. It offers a roadmap for aligning wellness tourism with Sustainable Development Goals (SDGs), ensuring both meaningful experiences for tourists and long-term benefits for host communities.